In Vitro Evaluation of a Stable Monomeric Gold(II) Complex with Hematoporphyrin IX: Cytotoxicity against Tumor and Kidney Cells, Cellular Accumulation, and Induction of Apoptosis - Georgi Momekov; Dilyan Ferdinandov; Spiro Konstantinov; Sonja Arpadjan; Daniela Tsekova; Galina Gencheva; Panayot R. Bontchev; Margarita Karaivanova (Bioinorganic Chemistry and Applications)
The antineoplastic potential of a stable monomeric Au(II) complex with hematoporphyrin IX (Hp), namely [Au(II)Hp-2H.(H2O)2], was investigated in a panel of tumor cell lines. The complex exhibits strong cytotoxicity, whereby the leukaemia- and lymphoma-derived cell lines are more sensitive, with IC50 values comparable to those of the reference anticancer drug cisplatin. In contrast, the solid tumor models are more sensitive to the platinum drug. A comparative assessment of both agents against the human kidney cell line 293T has shown that [Au(II)Hp-2H.(H2O)2] is less cytotoxic. The gold complex induces oligonucleosomal DNA fragmentation in tumour cells following 24-hour treatment and hence its cytotoxic effect is at least partly mediated by induction of apoptotic cell death. A prominent intracellular gold accumulation was detected after treating tumor cells with [Au(II)Hp-2H.(H2O)2] which shows that its putative pharmacological targets are readily accessible after a short incubation period.